MEASUREMENT OF THE NUCLEON STRUCTURE-FUNCTION F2 IN MUON-IRON INTERACTIONS AT 120, 250 AND 280 GEV - Aubert, J; Bassompierre, G; Becks, K; Best, C; Bohm, E; Debouard, X; Brasse, F; Broll, C; Brown, S; Carr, J; Clifft, R; Cobb, J; et al. (1981)
A measurement of the nucleon structure function F2 on iron is presented. The data cover a kinematic range of 3.25 {slanted equal to or less-than} Q2 {slanted equal to or less-than} 200 GeV2and 0.05 {slanted equal to or less-than} x {slanted equal to or less-than} 0.65. The data clearly show scaling violation. Fits in leading-order QCD have been made and values for the scale breaking parameter λ are given. © 1981.